Need-based training of community health officers for tuberculosis care in Ahmednagar district of Maharashtra, India: A before and after study - Mandar Padmakar Baviskar; Ankita Sinha; Shubhada S Javadekar; Rajvir Bhalwar (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Community health officers (CHOs) are a newly introduced cadre of mid-level health-care providers who will man the health and wellness centers under Ayushman Bharat Mission in India. Need-based training will help them fulfil their role in early diagnosis, treatment, and referral of tuberculosis (TB) patients. The present study identified the gaps in the awareness about TB in a heterogeneous group of trainees and addressed them through need-based training. MATERIALS AND METHODS: A before and after the study was carried out in 110 trainee CHOs at Rural Medical College, Loni. In-depth interviews were conducted with public health experts and focus group discussion was conducted with trainees to gain the quality inputs. Structured questionnaires based on training objectives specifically pertaining to TB were designed. Training was provided with an emphasis on addressing the gaps identified in the pretest. Posttest evaluation was done at the end of the training to assess its effectiveness. Data were analyzed using the SPSS software version. 17.0 (Inc., Chicago, IL, USA). RESULTS: The mean pretest score was 15.15 (standard deviation [SD] = 3.55) which improved after 6 months training to 24.01 (SD = 1.223), i.e., from 60% to 96%. There was highly significant improvement in overall knowledge score of trainees (t = 28.124, df = 109, P < 0.001). There was a statistically significant improvement in scores of all topics at the end of 6 months training in both Nursing and Ayurved graduates. Except for knowledge regarding the treatment of multidrug-resistant TB (P = 0.004), knowledge about all other topics was comparable in nursing and Ayurved graduates at the end. CONCLUSIONS: Needs assessment proved effective in identifying the gaps in knowledge and skills of interdisciplinary trainee CHOs. Medical colleges with expertise in teaching, training, and health service provision can work with the public health system to provide a model for rapid upgrading and capacity building to meet health-care challenges such as TB.